JURIDICAL ANALYSIS OF FINES AS AN EFFORT TO RECOVER LOSSES THE STATE IN THE CASE OF CORRUPTION (STUDY OF THE SUPREME COURT OF THE REPUBLIC OF INDONESIA DECISION NUMBER 2379 K/PID.SUS/2024) - Fadhil Fahreza; Panca Sarjana Putra; Adil Akhyar (Jurnal Ilmiah METADATA, 2026)
Criminal fines in the context of corruption can be an effort to recover state losses, although it is not the only way. Based on the results of the study, it is known that the judge's legal considerations in the Supreme Court of the Republic of Indonesia Decision Number 2379 K/Pid.Sus/2024 regarding the penalty of fines for the return of state losses in the case of corruption are that the defendant has enjoyed money from the crime, then the appropriate fine against the Defendant is Rp.200,000,000.00 (two hundred million rupiah) to Rp. 300,000,000.00 (three hundred million rupiah) because it is seen from the aspect of the State's losses is included in the low category and seen from the aspect of profit return is included in the low category because the Defendant only returns the State's losses less than 50% (fifty percent).